Virus-Like Particle Vaccines - Bachmann, Martin F; Vogel, Monique (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The structure, uniformity, stability, and functions of virus-like particles (VLPs) have encouraged scientists to utilize them as a unique tool in various applications in biomedical fields. Their interaction with the innate immune system is of major importance for the adaptive immune response they induce. The innate immune cells and molecules recognize and interact with VLPs on the basis of two major characteristics: size and surface geometry. VLP-based vaccines against hepatitis B, human papilloma, malaria, and hepatitis E have been developed and are available in many countries around the world. Given the inherent immunogenicity of VLPs, they render themselves ideal for the development of new vaccines against infectious diseases as well as noncommunicable diseases, such as chronic inflammation or cancer. This Special Issue is designed to provide an up-to-date view of the latest progress in the development of VLP-based prophylactic and therapeutic vaccines and technologies for their generation.